2022
DOI: 10.47836/pjssh.30.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Knowledge in Science: An Evaluation via Hydroponic Kit

Abstract: Every year, high school students response to choosing a science stream has indicated a declining pattern. It may be due to the lack of technical application of science that students cannot foresee, thus preventing them from having a clear vision of how science and technology could greatly help daily human life. The study aims to assess the knowledge of high school students through STEM education via a project-based learning method using the hydroponic kit. Seventy students from a government school in Kota Bhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…In the study by Wan Yusoff et al (2022), secondary school students in Malaysia demonstrated significant improvement in their knowledge of STEM education and hydroponic systems through project-based learning with hydroponic kits. This approach also exposed students to identifying and resolving hydroponic-related issues, fostering both knowledge acquisition and a heightened interest in science.…”
Section: Hydroponics In Educationmentioning
confidence: 99%
“…In the study by Wan Yusoff et al (2022), secondary school students in Malaysia demonstrated significant improvement in their knowledge of STEM education and hydroponic systems through project-based learning with hydroponic kits. This approach also exposed students to identifying and resolving hydroponic-related issues, fostering both knowledge acquisition and a heightened interest in science.…”
Section: Hydroponics In Educationmentioning
confidence: 99%